If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2 + i)(-2 + -1i) = 0 Multiply (-2 + i) * (-2 + -1i) (-2(-2 + -1i) + i(-2 + -1i)) = 0 ((-2 * -2 + -1i * -2) + i(-2 + -1i)) = 0 ((4 + 2i) + i(-2 + -1i)) = 0 (4 + 2i + (-2 * i + -1i * i)) = 0 (4 + 2i + (-2i + -1i2)) = 0 Combine like terms: 2i + -2i = 0 (4 + 0 + -1i2) = 0 (4 + -1i2) = 0 Solving 4 + -1i2 = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1i2 = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1i2 = 0 + -4 -1i2 = 0 + -4 Combine like terms: 0 + -4 = -4 -1i2 = -4 Divide each side by '-1'. i2 = 4 Simplifying i2 = 4 Take the square root of each side: i = {-2, 2}
| 5(x+y)=20+3y | | 24=-5x+6 | | 15+g=65 | | 5+4(x-1)=2x-9 | | 16/7=9/b | | -126-12x=50-4x | | u=vw+zforv | | 10x^2-2x-80=O | | c/40=5 | | 5/2x+8=10 | | 6c+15=-2c-16 | | -7/5x=-4 | | y-(-9)=5/3(x-33) | | 0.25y=24 | | 3/4h=15 | | 1/3x+1/5x+1/3=7/5 | | 4+w=48 | | 3x+17-5x=12-3(2x+1) | | 1.2(-1)+4.3=2.1-(-1) | | 15x-21=-7x | | 4=(2x+3) | | 2y=4x^2+8x+7 | | 88-38=47/5(h-7) | | 7x+2x=9-1 | | 1/2(x+16)=2/3(x-4) | | 5(x+1)=6(5x+7) | | -76-2x=80+10x | | -10=5/9p | | 8x=-144 | | x+27+2x-39=180 | | -2x+5-2x=13 | | 4+6y=6-4y |